The culture of consumption and excessive indebtedness: a discussion on possible interventions of financial education (Research, Society and Development, 2022)
The difficulty in managing financial resources has led many Brazilians to indebtedness, as not everyone has the necessary knowledge to deal with money assertively. Added to this fact, the culture of consumption encourages consumerism, with endless desires and uncritical consumption, interfering with financial balance, acquiring goods that are not within the budget, which can lead to indebtedness. Financial Education, on the other hand, presents concepts and objectives against this problem, aiming at the balance of financial life, conscious consumption and savings. Thus, through qualitative research, a bibliographic survey was carried out considering the guiding question: How can Financial Education contribute to minimize the impacts of Consumerism and Indebtedness on society? The theoretical contributions Bauman (2001; 2008), Baudrillard (1985), Bourdieu (1983) and ENEF (2012), allowed a discussion of possible articulations between consumerism and indebtedness and the objectives of Financial Education in Schools, considering their contributions to consumption conscious and financial balance. It was inferred that Financial Education can contribute to the alleviation of problems with consumerism and indebtedness, using concepts and tools that stimulate skills and enable a reflective process on attitudes towards the balance of financial life.